1999
DOI: 10.1056/nejm199901143400201
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bilateral Prophylactic Mastectomy in Women with a Family History of Breast Cancer

Abstract: In women with a high risk of breast cancer on the basis of family history, prophylactic mastectomy can significantly reduce the incidence of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
278
0
20

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,257 publications
(303 citation statements)
references
References 30 publications
5
278
0
20
Order By: Relevance
“…20,21 The present findings extend and confirm the preliminary report from the same series. 5 The results indicate that groups of patients may benefit differently from the surveillance programmes and treatment given so far.…”
Section: Discussionsupporting
confidence: 92%
“…20,21 The present findings extend and confirm the preliminary report from the same series. 5 The results indicate that groups of patients may benefit differently from the surveillance programmes and treatment given so far.…”
Section: Discussionsupporting
confidence: 92%
“…Identification of these individuals before they present with cancer is important since prophylactic surgery can reduce morbidity and mortality in these individuals (Struewing et al, 1995;Rebbeck et al, 1999;Hartmann et al, 1999;Hartmann et al, 2001;Meijers-Heijboer et al, 2001;Kauff et al, 2002;Rebbeck et al, 2004). Unfortunately, genetic testing is expensive, family history of breast cancer is common and BRCA mutations are rare (Ford et al, 1994;Peto et al, 1999;Antoniou et al, 2002).…”
mentioning
confidence: 99%
“…However, studies have suggested that total mastectomy provides the greatest breast cancer risk reduction due to removal of more breast tissue [19]. These surgeries are highly effective as bilateral prophylactic mastectomy has been shown to reduce the risk of breast cancer by at least 95% in women who have a deleterious mutation in the BRCA1 gene or the BRCA2 gene [20][21][22][23], while bilateral prophylactic salpingo-oophorectomy has been shown to reduce the risk of breast cancer by approximately 50% in women who have high risk of developing the disease [19].…”
Section: Risk-reducing Surgerymentioning
confidence: 99%